Plant parasitic nematodes of the families Merliniidae, Telotylenchidae and Pratylenchidae (Nematoda: Tylenchoidea) associated with important field crops of Gorgan region - A. Saeedi; M. Abdolahi; R. Ghaderi; R. Ghaderi; H. Charegani (گیاه‌پزشکی, 2019)
Background and Objectives Gorgan in Golestan province is substantially considered as an important region for production of agricultural crops in Iran. Plant-parasitic nematodes may cause direct or indirect damages to the plants in this region. Although some members of Merliniidae, Telotylenchidae or Pratylenchidae (Nematoda: Tylenchoidea( have been reported from different crops of Gorgan so far, there is no adequate and accurate information on these nematodes in association with many agricultural crops in Gorgan for making decisions on their management. The aim of the present study is to identify plant-parasitic nematodes of these three families in the agricultural field crops of Gorgan region and to determine their frequencies in the studied area. Materials and Methods In order to identify the plant parasitic nematodes from the families of Merliniidae, Telotylenchidae and Pratylenchidae associated with the important field crops of Gorgan, Iran, 64 soil samples were collected from different parts of the region during 2014-2015. The nematodes were extracted, fixed and transferred to anhydrous glycerin. The permanent slides were prepared from the extracted nematodes and necessary measurements were made. Finally, the nematodes were identified based on morphological and morphometric characters, using available identification keys. Results In this study, 11 species belonging to seven genera were identified as Amplimerlinius macrurus, Merlinius brevidens, M. microdorus, Paramerlinius hexagrammus and Pratylenchoides ritteri from family Merliniidae, Tylenchorhynchus brassicae and T. crassicaudatus from family Telotylenchidae, and Pratylenchus neglectus, P. sefaensis, P. thornei and Zygotylenchus guevarai from family Pratylenchidae. Tylenchorhynchus crassicaudatus was found in the rhizosphere of soybean plants in Gorgan. Description, morphometrics, line drawings and photomicrographs were provided for this new record of nematodes. Among the identified species, P. sefaensis, M. brevidens and M. microdorus were the most distributed species, with 26.6, 25.0 and 23.4 % relative frequencies, respectively. Discussion Tylenchorhynchus crassicaudatus is reported for the first time in Iran and cited here. Furthermore, differences of morphological and morphometric characters of this species with other closely related species namely T. thermophiles, T. paratriversus, T. kashmirensis and T. mashhoodi are discussed. The morphological and morphometric characters of the present population are congruent to those of the type population type, except for hyaline region of tail being slightly shorter (4-7 vs 7-13 µm). Our population differs from the closely related species in some features related to female tail (shape, length and the number of annuli on the ventral side), in the absence of post-rectal sac, spicules and gubernaculum lengths, distance of DGO from stylet knobs and position of vulva.